Clinical comparison of metrizamide and iopamidol for myelography. - Turski, P A; Sackett, J F; Gentry, L R; Strother, C M; Matozzi, F (American Journal of Neuroradiology, 1983)
A double-blind parallel comparison of iopamidol and metrizamide for myelography was performed in 36 patients. Sixteen adverse reactions were noted in 10 patients who received metrizamide. Six adverse reactions were reported in five patients who received iopamidol. There was no appreciable difference in the radiographic opacification.